A descriptive study of the physical characteristics of the southeastern region (a field study in the state of Biskra) - hadouche, aissa (sports creativity, 2025)
This study aimed to identify the physical and anthropometric characteristics of different regions in the Biskra province, thereby facilitating selection and guidance based on the specific characteristics of each region. To this end, the results obtained from seven different regions were compared to pinpoint the differences between them. The researcher employed a descriptive comparative approach, deemed most suitable for the nature and objectives of the study. The sample consisted of 613 students aged 9-11 years, distributed across the third, fourth, and fifth grades of primary school. The following tests were used: height and weight measurement, 30-meter speed, 1000-meter endurance, upper and lower limb strength, and trunk flexibility. After data collection, the data were analyzed using the SPSS statistical software. The researcher found statistically significant differences among the seven regions in height, endurance, speed, strength, and flexibility. However, no statistically significant differences were found among the seven regions in weight. The researcher recommended the need to adopt the results of the current study and use them in the processes of purification and discovery of young talents and to guide the process of establishing sports facilities and specialized sports frameworks according to the characteristics of each region.